Mould insert fabrication of a single-mode fibre connector alignment structure optimized by justified partial metallization. (4th February 2015) - Wissmann, Markus; Barié, Nicole; Guttmann, Markus; Schneider, Marc; Kolew, Alexander; Besser, Heino; Pfleging, Wilhelm; Hofmann, Andreas; Van Erps, Jürgen; Beri, Stefano; Watté, Jan
Abstract: For mass production of multiscale-optical components, microstructured moulding tools are needed. Metal tools are used for hot embossing or injection moulding of microcomponents made of a thermoplastic polymer. Microstructures with extremely tight specifications, e.g. low side wall roughness and high aspect ratios are generally made by lithographic procedures such as x-ray lithography or deep proton writing. However, these processes are unsuitable for low-cost mass production. An alternative manufacturing method of moulding tools has been developed at the Karlsruhe Institute of Technology (KIT). This article describes a mould insert fabrication and a new replication process for self-centring fibre alignment structures for low loss field installable single-mode fibre connectors, developed and fabricated by the Vrije Universiteit Brussel (VUB) in collaboration with TE Connectivity. These components are to be used in fibre-to-the-home networks and support the deployment and maintenance of fibre optic links. The special feature of this particular fibre connector is a self-centring fibre alignment, achieved by means of a through hole with deflectable cantilevers acting as micro-springs. The particular challenge is the electroforming of through holes with a centre hole diameter smaller than 125 µ m. The fibre connector structure is prototyped by deep proton writing in polymethylmethacrylate and used as a sacrificial part. Using joining, physical vapour deposition and electroforming technology, a negative copy of the prototyped connector is transferred into nickel to be used as a moulding tool. The benefits of this replication technique are a rapid and economical fabrication of moulding tools with high-precision microstructures and a long tool life. With these moulding tools low-cost mass production is possible. We present the manufacturing chain we have established. Each individual manufacturing step of the mould insert fabrication will be shown in this report. The process reliability and suitability for mass production was tested by hot embossing.